Development of Hand Out Mixed Completed List of Terms in The Material of Diversity of Life Organization Systems for Class VII Students First Medium School - Rani Selvia; Muhyiatul Fadilah; Abdul Razak (ATRIUM PENDIDIKAN BIOLOGI, 2017)
The purposes of this research are to result and show the validity and practicality of biology hand out with a complete cross- guided investigation on diversity of material life organization system for junior high school students. This study uses three steps of the 4D model is to determine, design, and develop. The subjects of this study is 4 validator, consist of lecture 2 and  2 teacher  in Biology and Education and 35 students of class VII SMP 15, Padang. The data in this study are primary data collected from the questionnaire validity and practicality. The validity of criteria gained; 88.32 % in the valid criteria, practicality by teachers was 90.41 % in practice criteria, and practicality by the students was 83.08 % in practice criteria